Effect of corn grits:soybean ration on solubility, dispersibility and emulsifying properties of dehydrated porridges - Wang, Sin-Huei; Borges, Geraldo Gonçalves; Cabral, Lair Chaves; Araújo, Flávia Batista (Pesquisa Agropecuaria Brasileira, 2001)
Dehydrated corn grits-soybean porridges at different proportions (100:0; 90:10; 80:20; 70:30; 60:40 e 50:50%) were assessed for nitrogen solubility index (NSI), protein dispersibility index (PDI), emulsifying activity (EA) and emulsion stability (ES) in order to verify their potential use as food ingredients. Dehydrated porridge was manufactured by soybean seed dehulling, blanching, disintegration of bleached corn grits and soybean, homogenization and spray drying. The results indicated that increasing soybean proportion from 0 to 50% caused an increase in the soluble nitrogen in water, NSI, dispersible protein in water and PDI, and a slight decrease in the EA and ES. No trypsin inhibitor activity was detected in studied dehydrated porridges.